Global transcriptomic response of Listeria monocytogenes exposed to Fingered Citron (Citrus medica L. var. sarcodactylis Swingle) essential oil. (May 2021) - Guo, Jiajing; Hu, Xiao; Gao, Zhipeng; Li, Gaoyang; Fu, Fuhua; Shang, Xuebo; Liang, Zengenni; Shan, Yang
Graphical abstract: Highlights: Fingered Citron essential oil exhibited significant anti-listeria activity. Obvious alterations of cell morphology were observed by SEM and TEM. The responses of L . M were explored by transcriptome analysis after exposure to FCEO. Chemotaxis and flagella assembly were significantly enhanced. The uptake of carbohydrates and metallic cations changed significantly. Abstract: Listeria monocytogenes, which could cause severe disease of listeriosis, is one of the most concerned foodborne pathogens worldwide. Citrus medica L. var. sarcodactylis Swingle (Fingered Citron) is one of the citrus species cultivated in south China. Here, we investigated the efficacy of Fingered Citron essential oil (FCEO) against L. monocytogenes and explored the response of L. monocytogenes in the presence of FCEO using genome-wide transcriptome analysis. FCEO exhibited strong anti-listeria activity and obvious alterations of cell morphology were observed by scanning electron microscopy and transmission electron microscopy. Moreover, GO analysis demonstrated many potential cell responses, including metabolic process, cellular process, single-organism process, cell part, membrane, catalytic activity, binding, and transporter activity. KEGG analysis suggests that L. monocytogenes respond and adapt by (1) increasing motility through the enhancement of flagella rotation; (2) promoting cell tumbles and re-orientating to escape from FCEO; (3) enhancing the uptake of carbohydrates from environment to gain more energy; (4) changing the uptake of several metallic cations, including iron, zinc, cobalt, and nickel. Our research contributes to the understanding of the adaptive responses of L. monocytogenes exposed to FCEO and provides novel insights for finding new targets of anti-listeria therapy.